Time value of money and the chronological revelations on riba in the quran (2016)
While some Scholars are of the view that Islam permits simple interest but frowns at compound interest due to time value of money, many consider both to be prohibited. It is against this backdrop that the paper examines and interprets the meaning of the word riba in the contexts in which they are used in the four places in the Qur’an and the Hadith. Using the analysis in these sources, the study finds that ad'afan mudd ‘afah in Q3:130 means a continual increment which could lead to the doubling and re-doubling of the original capital against confining it to compound interest. Our analysis shows that the usury that was forbidden for the Jews was the same with the usury of the pre-Islamic period that was banned for Muslims. It is noted that the Qur’an (Q2:278-279) prohibits all forms of riba, simple or compound, at the beginning of the contract or at the due date. The paper reveals that Islam does not attach value with time. Spot market where commodity and price are exchanged simultaneously is in line with the dictates of Islam. However, it is allowed to postpone delivery of commodity or price. Both cannot be delayed. Our analysis shows that if the same commodity is being exchanged, there should be equality in quantity and prompt delivery. By making the quantity equal, the quality has been ignored. If the quality is to be considered, both the qualities need to be converted into money and exchanged at market prices. If the commodities being exchanged are different, then there should be prompt delivery. Keywords: Riba, time value of money, Qur’an, Hadith, interest.